Tindak Pidana Penghinaan Lambang Negara Perspektif Hukum Positif dan Hukum Islam - Daimul Ikhsan; Anindita Ari Fatojanah; Bety Wulandari; Nur Hana Fitri; Khoirunnisa Utami (Academica: Journal of Multidisciplinary Studies, 2017)
This article was written to examine the action of national identity humiliation that recently happens, considered from the perspective of positive and Islamic law. Using descriptive approach method by analyzing the sources that relevant with the positive and Islamic law. From the analysis of the collected data, shows that the action of national identity humiliation is categorized as criminal action. Every citizen should appreciate and respect to the national symbol as the patriotism actualization.Â Keywords :National identity humiliation, Positive-law, Islamic-lawÂ